2019
DOI: 10.1111/cup.13438
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid dendritic cells in granulomatous variant of mycosis fungoides

Abstract: Introduction Granulomatous mycosis fungoides (MF) is a rare variant in which granulomas are associated with other typical signs of MF. Its prognosis is worse than that of classical MF. Plasmacytoid dendritic cells (PDCs) are a subset of interferon‐producing dendritic cells that link the innate and the adaptative immune responses. They have also been related to tolerance to certain tumors such as melanoma. Materials and methods In this article, we examined for the presence of CD123+ PDC in six cases of granulom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
(76 reference statements)
0
2
0
Order By: Relevance
“…Previous two studies of Pileri et al showed that PDC was rare in MF patients, but when the stages were compared, it is significantly higher in stage IIB than stage IA/B disease [37]. The cluster of CD123+ PDC was detected in 3 of 6 patients with granulomatous MF and it implies CD123 immunoreactivity could be identified in granulomatous MF [24]. Additionally, recent studies showed that CD123+ PDCs tend to contribute to cuta- neous granulomatous disorders such as granuloma annulare, granulomatous foreign body reactions, and even cutaneous sarcoidosis [38][39][40].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Previous two studies of Pileri et al showed that PDC was rare in MF patients, but when the stages were compared, it is significantly higher in stage IIB than stage IA/B disease [37]. The cluster of CD123+ PDC was detected in 3 of 6 patients with granulomatous MF and it implies CD123 immunoreactivity could be identified in granulomatous MF [24]. Additionally, recent studies showed that CD123+ PDCs tend to contribute to cuta- neous granulomatous disorders such as granuloma annulare, granulomatous foreign body reactions, and even cutaneous sarcoidosis [38][39][40].…”
Section: Discussionmentioning
confidence: 85%
“…Type 1 interferon produced by PDCs has a critical role in the onset, progression, and activation of autoimmune and immuno-allergic dermatoses, cutaneous neoplasms, and infectious diseases [13,19,22,23]. Surface expression of interleukin-3 receptor α chain (CD123), which is easily demonstrated by immuno- histochemical stains, is used in the differential diagnosis of LE cases to distinguish them from inflammatory/ autoimmune diseases [24][25][26][27]. The number and distribution of PDCs also differ markedly in inflammatory and neoplastic diseases.…”
Section: Discussionmentioning
confidence: 99%